Using Aloe Vera Gel (Aloe barbadensis Mill) as a Preservative to Increase the Stability of Vegetable Storage - Alsoufi, Mohammed Abdulrazzaq (Iraqi Journal of Science, 2024)
The aloe vera (ALV) gel coating solution contains tannins, alkaloids, flavonoids, coumarins, terpenes, saponins, and glycosides. The inhibition growth rates of Escherichia coli, Salmonella typhimurium, Staphylococcus aureus, and Bacillus subtilis were 63, 58, 65, and 57%, respectively, at a rate of 60.75% for a 5% ALV gel coating solution. It was 66, 63, 70, and 64%, respectively, at a rate of 65.75% for 10% ALV gel coating solution. It was 73, 68, 70, and 66%, respectively, at a rate of 69.25% for 20% ALV gel coating. The weight loss of coated eggplants with sterile distilled water, 5, 10, and 20% ALV gel coating solution was 0.791, 0.714, 0.578, and 0.384%, respectively, during storage for 10 days at 4°C, while it was 15.416, 13.638, 12.462, and 9.326%, respectively, during storage for 21 days at 25°C. The soluble solids content of coated eggplants with sterile distilled water, 5, 10, and 20% ALV gel coating solution was 5.9, 5.7, 5.6, and 5.4%, respectively, while it was 6.6, 6.1, 5.8, and 5.5%, respectively, whilst it was 6.9, 6.4, 6.0, and 5.6%, respectively, during storage for 10, 20, and 30 days at 4°C.